1998
DOI: 10.1063/1.475575
|View full text |Cite
|
Sign up to set email alerts
|

A laser photolysis/time-resolved Fourier transform infrared emission study of OH(X 2Π,v) produced in the reaction of alkyl radicals with O(3P)

Abstract: The emission spectra of vibrationally excited hydroxyl radical products formed in the reactions of alkyl radicals with O(3P) atoms are detected using a laser photolysis/time-resolved Fourier transform infrared spectroscopy technique. For the reaction between oxygen atoms and ethyl, the radicals are produced simultaneously by the 193 nm photolysis of the precursors SO2 and diethyl ketone, respectively. The observed initial OH(v) product vibrational state distribution for the C2H5+O(3P) reaction is 0.18±0.03, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 32 publications
4
18
0
Order By: Relevance
“…As with most other radical + O reactions, only a few limited studies of the rate coefficients for the C 2 H 5 + O and C 2 H 3 + O reactions have been presented [19][20][21]. There have also been a few experimental and theoretical studies of the product distributions for these reactions [20][21][22][23][24][25]. The present theoretical predictions for the reaction rates provide useful new kinetic data for combustion modeling.…”
Section: Introductionmentioning
confidence: 81%
“…As with most other radical + O reactions, only a few limited studies of the rate coefficients for the C 2 H 5 + O and C 2 H 3 + O reactions have been presented [19][20][21]. There have also been a few experimental and theoretical studies of the product distributions for these reactions [20][21][22][23][24][25]. The present theoretical predictions for the reaction rates provide useful new kinetic data for combustion modeling.…”
Section: Introductionmentioning
confidence: 81%
“…Hoyermann et al did find significant production of OH + C 2 H 4 , along with CH 3 + H 2 CO and H + CH 3 CHO. However, since an inverted vibrational distribution had been found for OH formed in this reaction, 19 they attributed this channel to direct bimolecular abstraction, rather than formation and subsequent isomerization of ethoxy to CH 2 CH 2 OH followed by dissociation. This conclusion, if correct, indicates that high internal energy on the ground state of ethoxy does not, by itself, lead to significant dissociation to OH + C 2 H 4 .…”
Section: Discussionmentioning
confidence: 99%
“…2,18 The reaction of O( 3 P) with ethyl radical, which can lead to the formation of the ethoxy radical with a great deal of excess energy, has been the subject of several experimental studies. [2][3][4]18,19 The fragmentation of chemically activated ethoxy radical formed in the reactions of ethyl radical with O, O 3 , and NO 3 was compared, 2 and it was found that both CH 3 + CH 2 O and H + CH 3 CHO were formed in all cases. The internal energy of the ethoxy radical formed in these reactions was peaked at roughly 4.0, 2.5, and 1.5 eV, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They improved the signal-to-noise ratio by pulse-to-pulse normalization through detection of the total infrared fluorescence produced on each laser pulse. The system has been applied to studies of the OH emission in the X 2 P (v < 5) states [11] and NH 2 emission in the à state [12].…”
Section: Introductionmentioning
confidence: 99%